Intergenerational Encounters: a Service-Learning Module for Postgraduate Students - Puntil, Donata; Dias, Gisele; Kralj, Carolina; Zunszain, Patricia A. (INSTED: Interdisciplinary Studies in Education & Society, 2022)
This paper illustrates the setting up and the delivery of a service-learning module designed to promote wellbeing at King’s College London during the academic year 2020–21, whereby postgraduate students engaged with a local community of older adults within a pensioner centre. Students and the community partners were conceived as active co-creators of knowledge, working together towards reducing loneliness. During lectures, students were exposed to a theoretical input grounded on positive psychology, intercultural studies, language & intercultural awareness and qualitative methodologies of narrative and auto-biographical research, while interacting with the older adults through telephone conversations. The module was delivered in the context of COVID-19, which demanded a reshaping of its original format, which was grounded on in-person creative workshops with the community around the themes of reminiscence and memory. The COVID-19 lockdown regulations imposed a different, distance-learning format which was co-designed with the community partners. Nevertheless, the phone conversations allowed space for bio-digital encounters and for unexpected intra-actions to emerge. The module’s assessment included a self-reflective e-Portfolio and a Digital Project, where students represented their own voices and the stories of the older adults they engaged with. The paper concludes with a reflection on the value of transformative learning for all project participants, within and outside the academic context, and argues for the value of intergenerational encounters to tackle contemporary social issues, such as loneliness and mental health problems.